Coronaviruses with Special Emphasis on First Insights Concerning SARS - Schmidt, Axel.; Schmidt, Axel.; Wolff, Manfred H.; Wolff, Manfred H.; Weber, Olaf.; Weber, Olaf. (Birkhäuser Advances in Infectious Diseases,, 2005)
It is with great pleasure that we introduce the first volume of Birkhäuser Advances in Infectious Diseases.This book series focuses on relevant and trending topics in microbiology and infectious diseases with emphasis on emerging pathogens and related diseases.This interdisciplinary series presents latest advances and new approaches in molecular biology as well as insights into human and veterinary clinical medicine. Furthermore, matters in epidemiology, disease management, hygiene and prevention of infectious diseases are discussed. Emerging or novel pathogens are a grand challenge in medical science. Therefore, we focused the first volume of this series on the outbreak of SARS. The advent of SARS is a threat for people around the globe. Our modern technologies in communication and mobility have figuratively transformed the world into a village. This traffic, however, reprensents a new opportunity to spread diseases, particularly such of infectious nature from tiny villages throughout the entire world. In-depth knowledge of a novel pathogen's characteristics will help to manage or event prevent pandemias.